Interferon-γ-Producing CD4+ T Cells Drive Monocyte Activation in the Bone Marrow During Experimental Leishmania donovani Infection - Romano, Audrey; Brown, Najmeeyah; Ashwin, Helen; Doehl, Johannes S. P.; Hamp, Jonathan; Osman, Mohamed; Dey, Nidhi; Rani, Gulab Fatima; Ferreira, Tiago Rodrigues; Kaye, Paul M. (Frontiers in Immunology, 2021)
Ly6Chi inflammatory monocytes develop in the bone marrow and migrate to the site of infection during inflammation. Upon recruitment, Ly6Chi monocytes can differentiate into dendritic cells or macrophages. According to the tissue environment they can also acquire different functions. Several studies have described pre-activation of Ly6Chi monocytes in the bone marrow during parasitic infection, but whether this process occurs during experimental visceral leishmaniasis and, if so, the mechanisms contributing to their activation are yet to be established. In wild type C57BL/6 (B6) mice infected with Leishmania donovani, the number of bone marrow Ly6Chi monocytes increased over time. Ly6Chi monocytes displayed a highly activated phenotype from 28 days to 5 months post infection (p.i), with >90% expressing MHCII and >20% expressing iNOS. In comparison, in B6.Rag2-/- mice <10% of bone marrow monocytes were MHCII+ at day 28 p.i., an activation deficiency that was reversed by adoptive transfer of CD4+ T cells. Depletion of CD4+ T cells in B6 mice and the use of mixed bone marrow chimeras further indicated that monocyte activation was driven by IFN-γ produced by CD4+ T cells. In B6.Il10-/- mice, L. donovani infection induced a faster but transient activation of bone marrow monocytes, which correlated with the magnitude of CD4+ T cell production of IFN- and resolution of the infection. Under all of the above conditions, monocyte activation was associated with greater control of parasite load in the bone marrow. Through reinfection studies in B6.Il10-/- mice and drug (AmBisome) treatment of B6 mice, we also show the dependence of monocyte activation on parasite load. In summary, these data demonstrate that during L. donovani infection, Ly6Chi monocytes are primed in the bone marrow in a process driven by CD4+ T cells and whereby IFN-γ promotes and IL-10 limits monocyte activation and that the presence of parasites/parasite antigen plays a crucial role in maintaining bone marrow monocyte activation